Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0531
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Biosynthesis in Higher Plants

Abstract: Biosynthesis of the major biologically active gibberellins (GAs) in higher plants proceeds first in plastids via the tetracyclic diterpene hydrocarbon ent ‐kaurene, which is oxidised by membrane‐associated cytochrome P450 mono‐oxygenases to produce GA 12 and GA 53 on the endoplasmic reticulum. These intermediates are oxidised further by the soluble 2‐oxoglutarate‐dependent dioxygenases GA 20‐oxidase and GA 3‐oxidase to the active C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 191 publications
0
21
0
1
Order By: Relevance
“…Gibberellins stimulate cell division and expansion in response to light, thus promoting stem elongation (Gupta and Chakarabarty, 2013). The stem elongation stimulated by the GA 3 treatment is not directly related to flowering; however, in many species, transition to flowering triggers the stem elongation (Hedden, 2016). Even though Kalancho€ e species are traditionally used as potted plants, lately, there is increasing interest in using them as cut flowers because of their outstanding vase life (Queen, https://www.queen.dk/en).…”
Section: Growth Regulators Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibberellins stimulate cell division and expansion in response to light, thus promoting stem elongation (Gupta and Chakarabarty, 2013). The stem elongation stimulated by the GA 3 treatment is not directly related to flowering; however, in many species, transition to flowering triggers the stem elongation (Hedden, 2016). Even though Kalancho€ e species are traditionally used as potted plants, lately, there is increasing interest in using them as cut flowers because of their outstanding vase life (Queen, https://www.queen.dk/en).…”
Section: Growth Regulators Discussionmentioning
confidence: 99%
“…In many plants, the flowering response is closely linked to endogenous hormonal levels, which is directly or indirectly associated with their developmental stage (Bratzel and Turck, 2015). Gibberellins are a class of hormones that play multiple roles in plant growth and development, such as seed germination, stem elongation, leaf expansion, shortening of juvenile phase and floral transitioning, and fruit patterning (Hedden, 2016). Gaskin et al (1973) observed that the level of gibberellins increased considerably in Kalancho€ e daigremontiana when flower formation was induced.…”
mentioning
confidence: 99%
“…Gibberellic acid (GA 3 ) is a natural phytohormone that has promising applications in agriculture and in the horticulture industry due to its positive impact on plant growth and development [9]. GA 3 has been used as a plant growth regulator in different crops, ornamental plants, and orchards, exhibiting positive impacts for enhancing seed germination [10,11], flowering [12,13], endosperm mobility, leaf expansion, leaf development, shortening of juvenile phase, stem elongation, floral transitioning, and setting of flowers and fruits [14,15]. Foliar applications of GA 3 enhance the flower stem length in cut-flowers grown in soil [16].…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellins, which belong to the tetracyclic diterpenoid class of hormones, comprise a group of over 136 natural plant constituents [ 6 ], but only some of them, e.g. GA 1 , GA 3 , GA 4 , GA 5 , GA 6 and GA 7 exhibit biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellins play important roles in many aspects of plant growth and development, e.g. seed development and germination, somatic embryo germination and regeneration, stem elongation, leaf expansion and flower development [ 6 , 7 , 8 , 12 , 13 ]. Because somatic embryogenesis starts in most cases from leaf explants, so the primary status of gibberellin metabolism in leaf tissues should be considered with a particular attention.…”
Section: Introductionmentioning
confidence: 99%